Phylogeny of Lysiloma (Fabaceae), a genus restricted to Megamexico with outliers in the West Indies and Florida - Duno de Stefano, Rodrigo; Tun Tun, Christian; López Contreras , José Enrique; Carnevali Fernández-Concha, Germán; Leopardi-Verde, Carlos Luis; Ramírez-Prado , Jorge Humberto; Can Itza, Lilia Lorena; Tamayo Cen, Ivan (Instituto de Ecología, A.C., 2021)
Background and Aims: Lysiloma is a Neotropical genus in the Fabaceae family that comprises eight species, six of which are widely distributed in Mexico, and two more that occur in the Antilles and Florida. Lysiloma is frequent in Megamexico’s dry forests. A previous phylogenetic study included three species of Lysiloma and Hesperalbizia occidentalis. Both genera are closely related, but their divergence has weak support. Our objectives were to test the monophyly of the genus, evaluate the sister relationships within the genus, and estimate the divergence times. Methods: A phylogenetic analysis based on morphological characters, molecular markers (ETS, matK, and trnK), as well as a combined analysis (morphology + molecules) was performed. The data matrices were analyzed both individually and concatenated (total evidence approach) with Bayesian inference and Maximum Parsimony. In addition, molecular divergence times were estimated from the ETS dataset with a Bayesian uncorrelated lognormal relaxed clock. Key results: The morphological analysis supports the monophyly of Lysiloma with Hesperalbizia as sister group. However, the individual and the combined molecular analyses do not provide resolution to clarify the relationships between Hesperalbizia occidentalis, Lysiloma sabicu, and core Lysiloma. The total evidence analysis (including morphology) supports the monophyly of Lysiloma, yet with low support. According to our molecular clock model, the clade Lysiloma+Hesperalbizia diverged from other members of the tribe Acacieae+Ingeae about 32 million years ago, and the diversification of the core of Lysiloma occurred during the Miocene. Conclusions: Lysiloma+Hesperalbizia is an early divergent clade of tribes Acacieae+Ingeae. There are enough morphological differences to recognize both linages. Morphological characters informally used for taxonomic delimitation seem to have evolved homoplasiously. The clade Lysiloma and Hesperalbizia separated from other members of the tribe Acacieae+Ingeae in the Oligocene, but the diversification of the core of the genus coincides with the expansion of the dry forest at the beginning of the Miocene.